Urban-rural dichotomy in asthma - A.A. Awotedu (South African Family Practice)
Asthma is a chronic inflammatory disease of the airways, which is global in spread, affects all ages and both sexes. The prevalence rates vary from country to country and vary even in the same country between urban and rural areas.